Mayer-Rokitansky-Küster-Hauser (MRKH) Syndrome Presenting with Condylomata Acuminata in a 28 Years Old Zambian Woman: A Case Report - Mwanakasale, Victor; Balapala, Kartheek R; Kalolekesha, Memory C (British Journal of Healthcare and Medical Research, 2025)
We present a rare form of Differences in sex development (DSD) that presented with Human papilloma virus (HPV) infection. The case is that of Mayer-Rokitansky-Küster-Hauser (MRKH) syndrome presenting with condylomata acuminate in a 28 years old Zambian woman. The diagnosis was made clinically and in the operating theatre. The case underscores the importance of taking a thorough gynaecological history and physical examination in all female patients that present with sexually transmitted infections as rare DSD may be missed due to cultural barriers. Imaging techniques are key to confirming the diagnosis of DSD such as MRKH syndrome.